Structural Characterization of Mn3O4(001) Thin Films and Their Interaction with CO - Barreto, Jade; Fickenscher, Georg; Hohner, Chantal; Ramos, Maria I.; Annese, Emilia; Archanjo, Braulio; Achete, Carlos A.; Libuda, Jörg; Stavale, Fernando (Journal of Physical Chemistry C, 2024)
In this study, we investigated the atomic-level interaction between CO molecules and a well-ordered Mn3O4(001) thin film. The oxide film, initially grown on a single-crystal Au(111) substrate, was characterized using X-ray photoelectron spectroscopy (XPS) to determine its oxidation state. Further examination of the film structure through scanning transmission electron microscopy (STEM) and low-energy electron diffraction (LEED) revealed its growth orientation along the [001] direction, with three domains rotated by 60° and aligned with the ⟨110⟩Au directions. Notably, the termination of the film features a layer of Mn3+ cations covered with oxygen atoms. The study then focused on the interaction of the film with CO, employing infrared reflection absorption spectroscopy (IRAS) and temperature-programmed IRAS (TP-IRAS). The results unveiled two distinct IR peaks related to CO adsorption: one at 2140 cm-1, signifying that CO molecules weakly adsorbed on the oxygen-terminated surface of Mn3+ cations, and another at 2105 cm-1, indicative of CO molecules bound to Mn2+ cations at oxygen vacancies.
CRIS-Team Scopus Importer:2024-09-13